Histological Evidence of Oosorption in the Cold-water Coral Caryophyllia huinayensis from station X-Huinay, Comau Fjord, Chile - Bishal Leo Ademes; Thomas Heran; Ali Eissing-Al-Mukahal; Jürgen Laudien (PANGAEA, 2025)
During winter and spring 2019 and summer and fall 2021, a total of 40 specimens of the cold-water coral Caryophyllia (Caryophyllia) huinayensis were collected by scientific SCUBA divers at the study site—X-Huinay—in Comau Fjord, southern Chile. Specimens were sampled at water depths ranging from 23 to 30?m. Environmental parameters including temperature, salinity, dissolved oxygen concentration, and pH were recorded in situ at each site at the time of collection to characterize the ambient habitat conditions. This dataset was collected to provide insights into the reproductive processes and stress responses in cold-water corals under natural environmental variability, with particular focus on the phenomenon of oosorption, a form of oocyte resorption potentially associated with energetic trade-offs. All collected coral polyps were histologically processed: samples were fixed, embedded, sectioned, and stained with haematoxylin-eosin. Digital histological slides were generated from the stained sections using a Hamamatsu NanoZoomer S360 whole-slide scanner at 40 exttimes magnification (0.23?μm/pixel). The resulting Whole Slide Images (WSIs) were saved in NDPI format and amount to a total of approximately 547 GB of high-resolution image data. The scans were analyzed for signs of oosorption. The corresponding slides exhibiting this process are marked in the associated data table. This dataset provides a unique and high-resolution visual archive of cold-water coral reproductive tissues from a fjord system influenced by freshwater input, variable oxygen concentration, and seasonal environmental gradients. It may serve as a valuable resource for comparative histological studies, reproductive cycles, and stress responses in cold-water ecosystems.